2018
DOI: 10.3892/etm.2018.7083
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA PVT1 promotes glioma cell proliferation and invasion by targeting miR‑200a

Abstract: Glioma is a type of malignant tumor accounting for 80% of all brain cancer morbidity. The long non-coding RNA (lncRNA) PVT1 has been demonstrated to be an oncogenic lncRNA in other types of cancer. However, the role of PVT1 in glioma is still unknown. The aim of the present study was to investigate the role of PVT1 in glioma, and its potential association with microRNA (miR)-200a. miR-200a mimics and small interfering (si)RNA transfection were utilized to construct miR-200a overexpression and knockdown models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 29 publications
(42 reference statements)
1
28
0
2
Order By: Relevance
“…PVT1 is a long noncoding RNA (lncRNA) that when highly expressed is associated with progression and poor prognosis in a pan-cancer cohort from TCGA. PVT1 overexpression has also been associated with poor response to chemotherapy in gliomas and squamous cell carcinoma of the head and neck 5153 . In line with these findings, hypomethylation of the PVT1 promoter was detected in our IDH -eLB in association with overexpression of the correspondent gene in the worst prognostic subtype ( IDH wt), in both the TCGA and the current cohort samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PVT1 is a long noncoding RNA (lncRNA) that when highly expressed is associated with progression and poor prognosis in a pan-cancer cohort from TCGA. PVT1 overexpression has also been associated with poor response to chemotherapy in gliomas and squamous cell carcinoma of the head and neck 5153 . In line with these findings, hypomethylation of the PVT1 promoter was detected in our IDH -eLB in association with overexpression of the correspondent gene in the worst prognostic subtype ( IDH wt), in both the TCGA and the current cohort samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PVT1 modulated GREM1 and BMP downstream signaling proteins through sponging miR-128-3p, thereby promoting tumorigenesis and progression of glioma [24]. The overexpression of PVT1 in glioma tissue and cells and promotes glioma cell proliferation and invasion by targeting miR-200a [25]. PVT1 knockdown could negatively regulate miR-424 to inhibit human glioma cell activity, migration and invasiveness [26].…”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNAs could mediate various cellular biological functions including cell proliferation, apoptosis, migration, and invasion in pathology evolvement 7,8 . Increasing studies revealed the implication of lncRNAs in progression of brain tumors 9,10 . To date, the molecular relationship between lncRNA and glioma onset and progression has been unveiled.…”
Section: Introductionmentioning
confidence: 99%